Acemannan-induced tooth socket healing: A 12-month randomized controlled trial - Ngoc Bao Vu; Vannaporn Chuenchompoonut; Pornchai Jansisyanont; Polkit Sangvanich; Thanh Ha Pham; Pasutha Thunyakitpisal (Elsevier, 2021)
Background/purpose: Natural compounds have become alternatives for bone regeneration. Acemannan, the main polysaccharide extracted from Aloe vera, has been demonstrated as a promising osteoinductive material in vitro and in vivo. This clinical study investigated the effect of acemannan on tooth socket healing. Materials and methods: Thirty-five otherwise healthy patients, 18-25 years old and diagnosed with horizontal or vertical partial impaction of the lower third molars, were enrolled in this randomized controlled trial. After removing the teeth, the sockets randomly received one of the following treatments: spontaneous blood-clotting (control), 20 mg acemannan sponge, or 50 mg acemannan sponge. Cone-beam computed tomography of the mandible was performed immediately (baseline), and at 3-, 6-, and 12-months postoperatively; the data were analyzed using the OsiriX MD program. Bone healing in the socket was determined measuring the socket volume. One-way ANOVA was used to analyze the differences within each group and between groups. Results: Thirty-five patients with 43 partially impacted lower third molars participated in this study. No patients exhibited alveolar osteitis or secondary infection. Compared with baseline, all groups showed significant reduction in socket volume at all observation time-points (p < 0.05). The 50 mg acemannan group had a significantly greater reduction in socket volume compared with the control at all postoperative time-points (p < 0.05). The 20 mg group had a significantly greater reduction in socket volume compared with the control at 3-months postoperatively (p < 0.05). Conclusion: We conclude that acemannan increases bone healing at 3-, 6-, and 12-months after removal of partially impacted mandibular third molars.